Pengaruh Earning Per Share (EPS) dan Sales Growth terhadap Harga Saham Perusahaan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia - Nugrah Leksono Putri Handayani; Poppy Fitrijanti Soeparan; Mohammad Hidayatul Holili (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study evaluates the dynamics of stock price movements in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) over the 2021–2025 period by examining Earning Per Share (EPS) and Sales Growth indicators. Employing a quantitative causal-explanatory research design, the sample was selected using a purposive sampling technique, resulting in 10 companies with a total of 50 firm-year observations. Secondary data were gathered from published annual financial statements and secondary market closing stock prices, then processed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4. The empirical findings demonstrate that EPS has a positive and statistically significant effect on stock prices  ( ; ), Conversely, Sales Growth fails to show a significant effect on stock price fluctuations ( ; ). The coefficient of determination ( ) yields a value of 0.648, indicating that the independent variables account for 64.8% of the variance in stock prices, while the remaining 35.2% is explained by factors outside the estimated model. The practical implication of these findings underlines that capital market investors in the primary consumer goods sector tend to prioritize net earnings performance over mere sales volume expansion.